The Role of Supeltas in Improving Traffic Safety in Kartasura as an Implications of Developing School Security Patrol Skills - Isnaini, Dian Ratri Nur; Patmisari, P (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to describe the role of Supeltas officers (Traffic Control Volunteers) in enhancing road safety in Kartasura District by examining how their activities contribute to reducing accidents and increasing the security of all road users. Methodology: Employing a descriptive qualitative design, the researcher—serving as the key instrument—collected data through snowball sampling to identify knowledgeable participants, direct observations of Supeltas in action, in‐depth interviews with officers and community members, and documentation review. Data analysis followed a systematic process of collection, reduction, presentation, and conclusion‐drawing (verification) to ensure a clear focus on how Supeltas operate in the field. Results: Findings reveal that Supeltas significantly improve road safety by actively assisting pedestrians—especially schoolchildren— in crossing roads, thereby minimizing accident risks. Public perception of Supeltas is overwhelmingly positive, with community members appreciating their patience and guidance. However, challenges include reckless behavior by some drivers (notably students) who disregard traffic regulations. Supeltas address these issues through calm regulation and gentle reprimands to encourage compliance. Applications/Originality/Value: This research highlights the practical impact of volunteer‐based traffic control on community safety and underscores the need to support and expand Supeltas initiatives. By integrating Supeltas into extracurricular PKS programs and fostering broader community involvement—particularly among students—local authorities and schools can strengthen traffic safety education, reduce reckless driving, and prevent accidents in Kartasura and similar districts.